Early results of metal on metal articulation total hip arthroplasty in young patients - Mohamad, J.A.; Kwan, Mun Keong; Merican, A.M.; Abbas, A.A.; Kamari, Z.H.; Hisa, M.K.; Ismail, Z.; Idrus, R.M. (Malaysian Medical Association, 2004)
We report our early experience of 20 cases of metal on metal articulation total hip arthroplasty in 19 young patients. Avascular necrosis of the femoral head (63) was the commonest diagnosis for patients undergoing this procedure, followed by osteoarthritis (21). In general, most of the patients were young and physically active with an average age of 43.1 years (range, 25 to 58 years). The average follow-up period was 18 months (range, 7 to 46 months). The mean total Harris Hip Score preoperatively and at final follow-up was 31 points and 89 points respectively. The mean total Pain Score improved from an average of 11.5 to 41.1 points at final follow-up. Sixteen (84) of the patients had a good to excellent hip score. There was one dislocation, which stabilized after reduction and conservative management. One case of early infection underwent a two-staged revision.